1981
DOI: 10.1080/01647958108683257
|View full text |Cite
|
Sign up to set email alerts
|

A survey of chromosome complements in the Tetranychidae

Abstract: The chromosome numbers have been assessed for 31 bisexual species of 14 different genera of the Tetranychidae, bringing the total of karyotyped species in this family to 109. The taxonomic significance of karyotype information is discussed. A haploid number of n=5 occurs in Neotrichobia arizonensis, Eotetranychus fremonti and E. gambelii ; of n=4 in Marainobia spec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…It is to mention that arrhenotoky has also been demonstrated for the Tenuipalpidae and the Tetranychidae Helle et al, 1981).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is to mention that arrhenotoky has also been demonstrated for the Tenuipalpidae and the Tetranychidae Helle et al, 1981).…”
Section: Discussionmentioning
confidence: 92%
“…The Tetranychidae and Tenuipalpidae were rather thoroughly examined on karyotype earlier, and the main facts and conclusions can be found in Helle et al, (1981) and Bolland and Helle (1981). Of Eriophyidae, the gall mites, no species have been karyotyped thus far.…”
Section: Introductionmentioning
confidence: 98%
“…The division of these genera into subgeneric groups based on inconsistent morphological differences remains questionable. Helle et al . (1981) suggested that this historic sub­division was for practical rather than phylogenetic reasons and that it resulted in a somewhat artificial classification (Meyer 1987).…”
Section: Oligonychus On Grasses In Australiamentioning
confidence: 99%
“…The species reproduces by arrhenotoky, with diploid females and haploid males (Helle et al, 1981). The lifetime fecundity of females feeding on poinsettia leaves is 21, 51 and 32 eggs and the intrinsic rate of increase is 0.0988, 0.1731 and 0.1145 at 20, 24 and 28 °C, respectively (Lai and Lin, 2005).…”
Section: Reproductionmentioning
confidence: 99%